The Effect of Work Conflict, Quality of Work Life on Employee Performance with Organizational Citizenship Behavior as a Mediation Variable - Arief Lukman Hakim; Muryati; Adya Hermawati (Journal of Management Research and Studies, 2026)
This study aims to analyze the influence of Work Conflict and Quality of Work Life on Employee Performance, with Organizational Citizenship Behavior (OCB) as a mediating variable. The study was conducted on civil servants at the Pasuruan City Regional Secretariat, with a population of all employees and a sample of 81 respondents using a saturated sampling technique. Data were analyzed using software .Smart Partial Least Square (PLS). The results of the analysis show that: (1) Work Conflict does not have a significant effect on Employee Performance, (2) Quality of Work Life also does not have a significant effect on Employee Performance, (3) Work Conflict does not have a significant effect on OCB, (4) Quality of Work Life contributes positively to increasing OCB, (5) strong OCB has a positive influence on employee performance, (6) work conflict does not have a significant influence on employee performance mediated by OCB, and (7) Quality of Work Lifeplays an important role in improving employee performance, with OCB as a mediator that strengthens the relationship. This study emphasizes the importance of Quality of Work Life in improving employee performance through OCB, although Work Conflict does not show a significant influence.